August 1, 1930: Canadians Thrill to the Arrival of the First Dirigible - Mills, Sean (The Beaver, 2003)

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Patrimoine archéologique de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

James McGill of Montreal : citizen of the Atlantic world - Cooper, John Irwin (Borealis Press, 2003)
Keywords: Autochtones; Fourrure; Marchands; McGill, James

L'aménagement du territoire axé sur les transports en commun: le cas de la ligne de train de banlieue Montréal/Blainville - Côté, Stéphanie (Université de Montréal, 2003)
Keywords: Banlieue; Transport en commun

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Donald Alexander Smith (1820-1914) - Dansereau, Francyne; Fulleringer, Pat (Héritage Dorval, 2003)
Keywords: Hommes d'affaires; Smith, Donald

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

L'assurance mutuelle des fabriques de Montréal: partenaire du patrimoine religieux depuis 150 ans (1853-2003) - Demers, Michel (L'Assurance mutuelle des fabriques de Montréal, 2003)
Keywords: Assurance; Incendies; Églises

Commerce et crédit à l'Ile Jésus, 1734-75. Le rôle des marchands ruraux dans l'économie des campagnes montréalaises - Dépatie, Sylvie (Canadian Historical Review, 2003)
Keywords: Marchands; Île Jésus

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

Le Domaine. Une belle histoire qui se poursuit... Trois coopératives... Tout un début! - Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc, 2003)
Keywords: Chaurès-Louard, Berthe; Coopérative d'habitation de Montréal; La Familiale; Logement

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Navigation; Énergie hydraulique

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal)

Les marchés de Montréal: bouillon de cultures - Dubé, Catherine (Continuité, 2003)
Keywords: Marchés

Terminus ferroviaires et espace urbain: le Canadien Pacifique et la transformation de l'est de Montréal, 1870-1915 - Duchesne, Julie (Université du Québec à Montréal, 2003)
Keywords: Canadien Pacifique; Chemins de fer

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Le syndicalisme dans le commerce de l’alimentation: le cas de la grève chez Steinberg en 1975 - Durand, Caroline (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
Keywords: Grèves; Steinberg; Épicerie

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Patrimoine archéologique de Montréal, 2003)
Keywords: Logement; Marchands

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Patrimoine archéologique de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

Une archéologie des jardins: fouille archéologique au site Lemoyne-Leber (BjFj-49), 1991-1992: Vieux-Montréal et faubourgs - Ethnoscop; Ross, Brian (Patrimoine archéologique de Montréal, 2003)
Keywords: Jardins; Le Ber, Jacques; Le Moyne de Longueuil, Charles; Marchands; Site LeMoyne-LeBer

ROTH, IDA (Steinberg) - Fahrni, Magda (Dictionnaire biographique du Canada, 2003)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Logement; Quartiers; Verdun

Canadian Equity Risk Premium, 1923-2001 - Hineson, Lucas (Université Concordia, 2003)

Syndicats et collectivités dans la gouvernance locale: une recherche exploratoire à Montréal - Klein, Juan-Luis; Fontan, Jean-Marc (Recherches sociographiques, 2003)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Systèmes locaux et réseaux productifs dans la reconversion économique: le cas de Montréal - Klein, Juan-Luis; Tremblay, Diane-Gabrielle; Fontan, Jean-Marc (Géographie, Économie, Société, 2003)

Pointe-à-Callière: le marché, façon XVIIIe - Labrosse, Francine (Continuité, 2003)
Keywords: Marchés; Musée Pointe-à-Callière; Musées

Le grain, la meule et les vents: le métier de meunier en Nouvelle-France - Laperle, Dominique (GID, 2003)
Keywords: Meunerie

La performance de Montréal et l'économie du savoir: un changement de politique s'impose - Lapointe, Alain (HEC Montréal, Institut d'économie appliquée, 2003)

Le Royal Insurance Building: recherche archéologique au site BjFj-22, 1990: Vieux-Montréal et faubourgs - Les recherches Arkhis (Patrimoine archéologique de Montréal, 2003)
Keywords: Assurance; Pointe-à-Callière; Royal Insurance

Montréal ou la traversée du désert - Linteau, Paul-André (Les Affaires, 2003)

Patrimoine industriel: le souffle de l’art - Lord, Denis (Continuité, 2003)
Keywords: Patrimoine

After Notman: Montreal Views - A Century Apart / D'après Notman: Regards sur Montreal - Un siècle plus tard - Maciejewski, Andrzej (Firefly Books, 2003)
Keywords: Notman, William; Photographie

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Keywords: Redpath (famille); Redpath, John

L’apport des services de proximité à la construction d’une identité de quartier: analyse de services d’économie sociale et solidaire dans trois quartiers de Montréal - Morin, Richard; Rochefort, Michel (Recherches sociographiques, 2003)
Keywords: Centre-sud (quartier); Hochelaga (quartier); Maisonneuve (quartier); Plateau Mont-Royal; Quartiers

La nouvelle économie à la rescousse des métropoles industrielles. Analyse comparée des stratégies publiques à Montréal et à Glasgow - Poitras, Claire (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2003)
Keywords: Métropole

Pourquoi Toronto a surclassé Montréal au sommet de la hiérarchie urbaine canadienne? L’impact des différences culturelles sur la dynamique spatiale des services supérieurs - Polèse, Mario; Sheamur, Richard (Géographie, Économie, Société, 2003)
Le système urbain canadien a subi un bouleversement important après 1960. Montréal, qui trônait depuis toujours au sommet de la hiérarchie, a été supplantée par l’éternelle seconde, Toronto. De tels renversements sont inhabituels. La destinée de Montréal paraît encore plus surprenante quand on pense qu’aux États-Unis, New York est demeurée le principal centre des affaires et de la haute finance malgré le déplacement de la population et de l’activité économique vers l’ouest (et le sud). Nous commençons par remonter brièvement le fil des événements, en écartant certaines hypothèses. Pour comprendre les décisions de localisation des services supérieurs et des fonctions de direction (exercées par les sièges sociaux), nous nous servons d’un modèle qui fait ressortir les coûts de communication et les coûts de recrutement associés aux travailleurs hautement qualifiés. Nous analysons enfin la dynamique spatiale des fonctions de direction au sein de certaines industries au Canada de 1971 à 1996.

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Aqueduc; Énergie hydraulique

Marchés publics et structuration spatiale du commerce à Montréal: 1870-1900 - Rousseau, Dany (Université du Québec à Montréal, 2003)
Keywords: Marchés

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

L'implantation de la galerie d'art à Montréal: le cas de W. Scott & sons, 1859-1914. Comment la révision du concept d'œuvre d'art autorisa la spécialisation du commerce d'art - Sicotte, Hélène (Université du Québec à Montréal, 2003)
Keywords: Expositions; Peinture

Jardiner en Nouvelle-France - Tairraz, Monique (Continuité, 2003)
Keywords: Jardins

Exploration de l'articulation entre l'évaluation environnementale stratégique et l'étude des impacts sur l'environnement - Vallée, Lucie (Université du Québec à Montréal, 2003)

The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Ingénieurs; Port